Event-triggered mechanism based distributed cooperative power sharing control for micro-grid - SHU Jian; YANG Chaojie; ZHANG Huanqiang; YANG Yunfeng; LI Zhenming; YAN Yunfeng (Diance yu yibiao)
The priority of the micro-grid operating at the islanded mode is to maintain the balance of power supply and demand. In recent years, distributed power sharing control strategy is gradually become proper alternative to central control due to its flexibility and scalability. However, the conventional distributed power sharing control strategy highly depends on the continuous communication and decision making, which causes the wasteful usage of communication resources. To this end, this paper provides an event-triggered mechanism based distributed power sharing control strategy. By deducing the triggering condition according to the stability of the control system, this control strategy allows the controller to conduct the control action and communicate with its neighbors only when the triggering condition is met. Thus, the periodic communication is converted to aperiodic and intermittent, and hence the communication burdens can be reduced significantly. Eventually, simulation results validate the effectiveness of the proposed event-triggered mechanism based distributed power sharing control strategy. It is shown that the proposed control strategy can highly reduce the communication requirement while achieving the control objective, thus improving the efficiency of the control system.